Countering Modern Terrorism: Military and other Options - Ejime, Raphael (European Scientific Journal, ESJ, 2017)
Terrorism has been part of human development dating back to the era of the struggles for independence and liberation but still defy attempts at an accepted definition. Hence, it has become increasingly necessary for governments to tackle this menace by whichever counter-terrorism measures possible. However, one pivotal means is the use of military force introduced by the then President of the United States, George W. Bush through his “War on Terror” speech on September 20, 2001. This paper tries to assess the pros and cons of this measure and other counterterrorism strategies.